The Underrated Salivary Virome of Men Who Have Sex With Men Infected With HIV - Guo, Ying; Huang, Xiaojie; Sun, Xintong; Yu, Yixi; Wang, Yan; Zhang, Baojin; Cao, Jie; Wen, Shuo; Li, Yuchen; Wang, Xin; Cai, Siyu; Xia, Wei; et al. (Frontiers in Immunology, 2021)
Salivary virome is important for oral ecosystem, but there are few reports on people living with HIV. We performed metagenomic sequencing to compare composition and functional genes of salivary virobiota between one HIV-negative and four HIV-positive groups in which participants were all men who have sex with men (MSM) with different immunosuppression statuses (five samples per group) to find the evidence that salivary virobiota plays a role in the pathogenesis of oral disease. Acute-stage subjects achieved a positive result of HIV RNA, but HIV antibody negative or indeterminate, whereas individuals with mild, moderate, and severe immunosuppression exhibited CD4+ T-lymphocyte counts of at least 500, 200–499, and less than 200 cells/μL or opportunistic infection, respectively. The results showed the composition of salivary virus genera in subjects with mild immunosuppression was the most similar to that in healthy people, followed by that in the acute stage; under severe immunosuppression, virus genera were suppressed and more similar to that under moderate immunosuppression. Furthermore, abnormally high abundance of Lymphocryptovirus was particularly obvious in MSM with HIV infection. Analysis of KEGG Pathway revealed that Caulobacter cell cycle, which affects cell duplication, became shorter in HIV-positive subjects. It is worth noting that in acute-stage participants, protein digestion and absorption related to the anti-HIV-1 activity of secretory leukocyte protease inhibitor was increased. Moreover, in the severely immunosuppressed subjects, glutathione metabolism, which is associated with the activation of lymphocytes, was enhanced. Nevertheless, the ecological dysbiosis in HIV-positive salivary virobiota possibly depended on the changes in blood viral load, and salivary dysfunction of MSM infected with HIV may be related to CD4 counts. Ribonucleoside diphosphate reductase subunit M1 in purine metabolism was negatively correlated, though weakly, to CD4 counts, which may be related to the promotion of HIV-1 DNA synthesis in peripheral blood lymphocytes. 7-Cyano-7-deazaguanine synthase in folate biosynthesis was weakly positively correlated with HIV viral load, suggesting that this compound was produced excessively to correct oral dysfunction for maintaining normal cell development. Despite the limited number of samples, the present study provided insight into the potential role of salivary virome in the oral function of HIV infected MSM.